A comparative study of the scholastic performance of selected grade six, section one pupils in Baclaran district III, Paranaque City Division SY 2001-2002: implications on early childhood education programmes - Avedillo, Teresita Carmen P. Alidon (Parañaque City: Olivarez College, 2002)
The study was undertaken to assess the mathematics teaching in the four public Secondary Schools in the Division of Pasay, which will serve as a basis for a proposed training program. Specifically, it sought to answer the following questions: 1. What is the profile of the teacher respondents with respect to the following: a) civil status; b) educational attainment; c) year level presently handled; d) teaching experiences; e) number of students per class; f) seminar - workshop or training attended; g) performance rating; and 5. h) frequency of supervisor observation? 2. What are the instructional needs of the mathematics teachers with respect to: a) Pre-service training; and b) In-service training? 3. How do the teacher respondents deliver the teaching of mathematics with respect to: a) teaching methodologies; b) evaluation used; and c) instructional aids? 4. What are the major problems encountered by the mathematics teacher in the exercise of their functions as mentors in terms of: a) teaching methodologies; b) evaluation used; c) instructional aids; and d) in-service training? Is there a significant difference on the delivery of teaching mathematics with respect to.
Master Thesis
Keywords: Scholastic performance